PERBANDINGAN PEMAHAMAN KONSEP BILANGAN BULAT MENGGUNAKAN PROBLEM BASED LEARNING DAN THINK PAIR SHARE - Budianti, Yudi; Sundari, Kori; Putri, Nadira Victoria (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research was motivated by the continued use of the lecture method in mathematics learning, particularly in the topic of integer addition and subtraction in Grade 2 at SDN Tambun 05. Based on observations and interviews, it was found that the teacher had never implemented the Problem Based Learning or Think Pair Share models in classroom activities. Therefore, the researcher was interested in comparing students' conceptual understanding through the application of these two models. This study aims to determine the differences in conceptual understanding of integer addition and subtraction between students who were taught using the Problem Based Learning model and those taught using the Think Pair Share model. This research employed a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of students in class 2A as the first experimental group using the Problem Based Learning model, and students in class 2B as the second experimental group using the Think Pair Share model, with 28 students in each class. The results of the study showed a difference in conceptual understanding between the two groups. In class 2A, which used the Problem Based Learning model, the average post-test score of conceptual understanding was 84.71, while the pre-test score was 61.42, showing an increase of 23.29 points. In class 2B, which used the Think Pair Share model, the average post-test score was 79.85, while the pre-test score was 70.35, resulting in an increase of 9.5 points. Based on the results of the hypothesis test using the independent sample t-test, a significance value of 0.036 (p < 0.05) was obtained, indicating a significant difference in conceptual understanding between students who learned through Problem Based Learning and those who learned through Think Pair Share